Education on Providing Exclusive Breastfeeding to Breastfeeding Mothers at Talun Kenas Community Health Center in 2024 - CHAIRANI, SHINTA ANDRIA; YANTI, MUTIARA DWI; SIREGAR, GF GUSTINA; PURBA, TETTY JUNITA; ASNITA, VIRDA AYU; TAMBA, VERAWATI; HARIATI, ERNI (Jurnal Pengabdian Masyarakat Putri Hijau, 2024)
Abstract Providing exclusive breast milk (ASI) is a key nutritional strategy for the health of babies aged 0-6 months. Although global health recommendations emphasize the importance of exclusive breastfeeding, coverage in Indonesia is still low. This study aims to eval_uate the effectiveness of educational interventions in increasing knowledge and practice of exclusive breastfeeding among mothers at the Talun Kenas Community Health Center. The of Community Service activities is to increase the knowledge of mothers who have babies 0-6 months and mothers who are still breastfeeding, so that mothers can provide exclusive breastfeeding optimally.